Reconnecting with Nature in the Built Environment: The Roles of Biophilic and Biomimetic Urban Design - Awal Prasetyo; Hendro Prabowo; Wahyu Prakosa; Destri Maya Rani (International Journal of Engineering, Science and Information Technology, 2026)
Integrating nature into urban design has become a crucial approach for creating healthy, sustainable, and livable cities. This paper explores the multidimensional benefits and distinct roles of two transformative frameworks: Biophilic Design and Biomimetics. While both are rooted in nature, they offer complementary pathways. Biophilic Design focuses on human well-being, systematically integrating natural elements, light, and materials into the built environment to strengthen the innate human-nature connection, thereby improving mental and physical health, reducing stress, and enhancing social cohesion. In contrast, Biomimetics is a technical approach that solves complex urban challenges by emulating nature's models, principles, and ecological systems. It leads to innovative, efficient, and sustainable solutions, such as bio-inspired ventilation systems and materials that enhance urban resilience. The paper argues that moving beyond superficial greening, the synergistic application of Biophilic (human-centered) and Biomimetic (performance-centered) strategies enables a fundamental transformation towards regenerative, resilient, and dignified human settlements capable of addressing the pressing challenges of global urbanization and climate change.